Augmented Th17 Differentiation Leads to Cutaneous and Synovio-Entheseal Inflammation in a Novel Model of Psoriatic Arthritis - Yang, Lu (Arthritis Rheumatol, 2018)
OBJECTIVE: To introduce a novel pre-clinical animal model of psoriatic arthritis, R26STAT3C(stopfl/fl) CD4Cre mice, and investigate the role of Th17 cytokines in the disease pathogenesis. METHODS: We characterized a novel murine model of Th17-driven cutaneous and synovio-entheseal disease directed by T cell-specific expression of a hyperactive STAT3 allele. By crossing R26STAT3C(stopfl/fl) CD4Cre mice onto an IL-22 knockout background or treating them with a neutralizing antibody against IL-17, we interrogated how these Th17 cytokines contribute to disease pathogenesis. RESULTS: R26STAT3C(stopfl/fl) CD4Cre mice develop acanthosis, hyperkeratosis, and parakeratosis of the skin, as well as, enthesitis/tendonitis and peri-articular bone erosion in different joints accompanied by osteopenia. T cell-specific expression of a hyperactive STAT3C allele drives an augmented Th17 response in these animals. Careful characterization revealed an increase in osteoclast progenitor (OCP) cells and RANKL producing cells that contributed to the osteopenic phenotype observed in the mutant animals. Abrogation of Th17 cytokines, IL-17 or IL-22, improved both skin and bone phenotype in the R26STAT3C(stopfl/fl) CD4Cre mice, revealing a central role of Th17 cells in the regulation of OCP numbers and RANKL expression on stromal cells. CONCLUSION: Perturbation of the IL-23/Th17 axis instigates Th17-mediated inflammation in R26STAT3C(stopfl/fl) CD4Cre mice, leading to cutaneous and synovio-entheseal inflammation, and bone pathology highly reminiscent of psoriatic arthritis. Both IL-17A and IL-22 produced by Th17 cells play critical roles in promoting the cutaneous and musculoskeletal inflammation that characterizes psoriatic arthritis.